Case report: Sodium and chloride muscle channelopathy coexistence: A complicated phenotype and a challenging diagnosis - Pagliarani, Serena; Meola, Giovanni; Filareti, Melania; Comi, Giacomo Pietro; Lucchiari, Sabrina (Frontiers in Neurology, 2022)
Non-dystrophic myotonias (NDM) encompass chloride and sodium channelopathy. Mutations in CLCN1 lead to either the autosomal dominant form or the recessive form of myotonia congenita (MC). The main symptom is stiffness worsening after rest and improving by physical exercise. Patients with recessive mutations often show muscle hypertrophy, and transient weakness mostly in their lower limbs. Mutations in SCN4A can lead to Hyper-, Hypo- or Normo-kalemic Periodic Paralysis or to different forms of myotonia (Paramyotonia Congenita-PMC and Sodium Channel Myotonia-SCM and severe neonatal episodic laryngospasm-SNEL). SCM often presents facial muscle stiffness, cold sensitivity, and muscle pain, whereas myotonia worsens in PMC patients with the repetition of the muscle activity and cold. Patients affected by chloride or sodium channelopathies may show similar phenotypes and symptoms, making the diagnosis more difficult to reach. Herein we present a woman in whom sodium and chloride channelopathies coexist yielding a complex phenotype with features typical of both MC and PMC. Disease onset was in the second decade with asthenia, weakness, warm up and limb stiffness, and her symptoms had been worsening through the years leading to frequent heavy retrosternal compression, tachycardia, stiffness, and symmetrical pain in her lower limbs. She presented severe lid lag myotonia, a hypertrophic appearance at four limbs and myotonic discharges at EMG. Her symptoms have been triggered by exposure to cold and her daily life was impaired. All together, clinical signs and instrumental data led to the hypothesis of PMC and to the administration of mexiletine, then replaced by acetazolamide because of gastrointestinal side effects. Analysis of SCN4A revealed a new variant, p.Glu1607del. Nonetheless the severity of myotonia in the lower limbs and her general stiffness led to hypothesize that the impairment of sodium channel, Nav1.4, alone could not satisfactorily explain the phenotype and a second genetic “factor” was hypothesized. CLCN1 was targeted, and p.Met485Val was detected in homozygosity. This case highlights that proper identification of signs and symptoms by an expert neurologist is crucial to target a successful genetic diagnosis and appropriate therapy.